Using some statistical techniques to measure the level of environmental information - Farhad Ali Ahmed; Muhammad Mahmoud Faqi Hussein; Akhtar Khan Saber Hamad (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The study of the environment and the environmental information has been the interest of many researchers in many different fields, and many kinds of research and studies have been conducted for it. Despite the incredible interest in the environmental problems, wشhether and notional or international scale, the problems are increasing continuously. That being the result of wasting resources, and the ignorance regarding these resources, The only way to increase awareness about the importance of the environment condition is with the cooperation of the whole community, citizens, students, teachers, politicians,… etc. to acknowledge the problems of the human behavior and its influence on the environment. The problem of this research is trying to solve is to uncover the overall environmental. Awareness among the students in the college of Administration and Economics / Sulaimani University.The sample is a random selection of (264) students from all departments. Use some statistical technique to, Analyzing, the results show that the environmental problems come first according to the relative importance (87.11%) and secondly the environmental direction comes with the relative importance (83.61%) while the natural and human resources come third with a relative importance (81.64%) and finally the development part comes with fourth degree according to the relative importance (77.65%).